Monitoring drug Efficacy through Multi-Omics Research initiative in Alzheimer’s Disease (MEMORI-AD): A protocol for a multisite exploratory prospective cohort study on the drug response-related clinical, genetic, microbial and metabolomic signatures in Filipino patients with Alzheimer’s disease - Veeda Michelle M Anlacan; Fresthel Monica M Climacosa; Francis James A Gordovez; John Carlo B. Reyes; Ian Kim B Tabios; Rafael Vincent M Manalo; Joana Marie Ceripulo Cruz; Joannes Luke B Asis; Rozel B Razal; Mark Joseph M Abaca; Aira B Dacasin; Ayra Patrice N Espiritu; et al. (BMJ Open)
Introduction Dementia is one of the leading causes of disability among older people aged 60 years and above, with majority eventually being diagnosed with Alzheimer’s disease (AD). Pharmacological agents approved for dementia include acetylcholinesterase enzyme (AChE) inhibitors like rivastigmine, donepezil and galantamine and the N-methyl-D-aspartate (NMDA) receptor antagonist memantine, prescribed as monotherapy or in combination with each other, depending on the severity of disease. There is currently no available study demonstrating the clinical response to these drugs for AD in the Filipino population. Hence, this protocol aims to characterise the clinical, genetic, microbial and metabolic factors associated with drug responses to donepezil, rivastigmine and/or memantine for AD in a cohort of Filipinos with late-onset AD.Methods and analysis This protocol involves a multisite descriptive study that will use two study designs: (1) a descriptive, cross-sectional study to characterise the clinical profile of Filipino dementia patients with AD and (2) an exploratory prospective cohort study to investigate drug response-related genetic, gut microbiome and metabolome signatures of a subset of the recruited AD patients. At least 153 patients with mild or moderate AD aged 65 years old and above will be recruited regardless of their treatment status. A subset of these patients (n=60) who meet inclusion and exclusion criteria will be included further in the exploratory cohort study. These patients will be grouped according to their baseline medications and will be observed for treatment response in 6 months. The cognitive, functional and behavioural domains of patients and levels of functioning will be measured using different assessment tools. Drug responses of Filipino patients will then be investigated employing multi-omics technology to characterise genetic variations via whole exome sequencing, gut microbiome profile via shotgun metagenomic sequencing and metabolome profile via liquid chromatography with mass spectrometry.Ethics and dissemination The study has received ethical clearance from the Department of Health Single Joint Research Ethics Board (SJREB-2022–15). Results of psychometric scales will be made available to enrolled patients. The study results will be presented at national/international conferences and published in international peer-reviewed scientific journals, and summaries of the results will be provided to the study funders and institutional review boards of the three tertiary referral hospitals.Trial registration number Philippine Health Research Registry ID PHRR230220-0054116; ClinicalTrials.gov ID NCT05801380